Improved variable ordering for ROBDDs - Prasad, , PWC; Singh, , AK; Dominic, , MM (2003)
Present here is a novel algorithm for minimization of the Reduced Ordered Binary Decision Diagram (ROBDD) by finding the best variable ordering for any Boolean function. Selection of ordering relation is achieved by considering each sub functions.